Micromotor‐Based Biomimetic Carbon Dioxide Sequestration: Towards Mobile Microscrubbers. (4th September 2015) - Uygun, Murat; Singh, Virendra V.; Kaufmann, Kevin; Uygun, Deniz A.; de Oliveira, Severina D. S.; Wang, Joseph
Abstract We describe a mobile CO2 scrubbing platform that offers a greatly accelerated biomimetic sequestration based on a self‐propelled carbonic anhydrase (CA) functionalized micromotor. The CO2 hydration capability of CA is coupled with the rapid movement of catalytic micromotors, and along with the corresponding fluid dynamics, results in a highly efficient mobile CO2 scrubbing microsystem. The continuous movement of CA and enhanced mass transport of the CO2 substrate lead to significant improvements in the sequestration efficiency and speed over stationary immobilized or free CA platforms. This system is a promising approach to rapid and enhanced CO2 sequestration platforms for addressing growing concerns over the buildup of greenhouse gas.